HUBUNGAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG INSPEKSI VISUAL ASAM ASETAT (IVA) DENGAN MINAT DALAM MELAKSANAKAN PEMERIKSAAN IVA - Ferdina, Cucun Setya (Judika (Jurnal Nusantara Medika), 2019)
ABSTRACT Cervical cancer is one of the most common types of cancer in women, with an estimated 570,000 new cases in 2018, which represents 6.6% of all cancers suffered by women. The high number of deaths from cervical cancer in Indonesia is caused by 95% of women not undergoing an early examination, causing a delay in the diagnosis of cervical cancer and decreasing women's life expectancy. This study aims to determine the relationship of knowledge of childbearing age woman about visual inspection with acetic acid (VIA) with interest in conducting VIA examinations in Campurejo Village of Kediri City. The research design used in this study was cross sectional analytic, the variable of this research are the knowledge of childbearing age woman about VIA and interest in conducting VIA examinations. The sample in this study were 134 women, using a simple random sampling technique. Data collection was obtained through giving questionnaires to respondents, which contained closed questions about the knowledge of women of childbearing age about VIA and the interest of childbearing age woman in conducting IVA examinations. The results of the study were then analyzed by the Spearman correlation test using SPSS. The results of the study showed that the research subjects had good knowledge of VIA and high interest in conducting VIA examinations. Generated r = 0.358 with p-value = 0,000 <α = 0.05. Then H0 is rejected and H1 is accepted, which means that there is a significant relationship between knowledge about VIA and interest in conducting VIA examinations in Campurejo Village, Kediri City. Keywords: knowledge, interests, cervical cancer, VIA